Variational analysis of Kirchhoff equations in Musielak-Orlicz-Zygmund spaces - El OUARDANI, Ahmed; ABERQI, Ahmed; ELMASSOUDI, Mhamed (Studia Universitatis Babeș-Bolyai Mathematica, 2026)
We study a class of nonlocal Kirchhoff problems with nonlinearities exhibiting nonstandard growth. Using variational methods in Musielak-Orlicz Zygmund spaces, we prove the existence of nontrivial weak solutions. The analysis uses generalized N-functions, Orlicz-Zygmund embeddings, pseudo-monotone operators, and the Palais-Smale condition, which allow handling double-phase and nonlocal Kirchhoff terms. The results extend classical variational methods to settings with borderline and logarithmic growth. Mathematics Subject Classification (2010): 35J60, 58J05. Received 03 December 2025; Accepted 18 February 2026.